2014
DOI: 10.1039/c4ra10726h
|View full text |Cite
|
Sign up to set email alerts
|

In search of new reconstructions of (001) α-quartz surface: a first principles study

Abstract: Using Born–Oppenheimer molecular dynamics simulations and “static” density functional theory calculations, reconstructions of the (001) α-quartz surface are studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 37 publications
9
44
0
Order By: Relevance
“…2NNMEAM + Qeq DFT [130] Si The volumetric thermal expansion coefficient is calculated to be 2.0 × 10 −5 , 2.7 × 10 −5 , and 2.3 × 10 −5 K −1 for rutile, anatase, and brookite, respectively, which is comparable with experimental values, 2.46 × 10 −5 and 1.45 × 10 −5 K −1 for rutile [132] and anatase [87], respectively. In a way similar to the TiO 2 polymorphs, we examine the change in internal energy of other Ti x O y compound phases as shown in Figs.…”
Section: Surfacesupporting
confidence: 77%
See 2 more Smart Citations
“…2NNMEAM + Qeq DFT [130] Si The volumetric thermal expansion coefficient is calculated to be 2.0 × 10 −5 , 2.7 × 10 −5 , and 2.3 × 10 −5 K −1 for rutile, anatase, and brookite, respectively, which is comparable with experimental values, 2.46 × 10 −5 and 1.45 × 10 −5 K −1 for rutile [132] and anatase [87], respectively. In a way similar to the TiO 2 polymorphs, we examine the change in internal energy of other Ti x O y compound phases as shown in Figs.…”
Section: Surfacesupporting
confidence: 77%
“…According to the present potential, the cotunnite transforms to another TABLE XIV. Calculated (0001) surface energy (J/m 2 ) of αquartz in comparison with first-principles data [130]. The Siterminated surface is unstable.…”
Section: Thermal Stability and Thermal Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…2. Further structural optimization has recently been reported that used Born-Oppenheimer molecular dynamics simulations and DFT [19].…”
Section: Silica and Silicatesmentioning
confidence: 99%
“…In theoretical works “dense surface” with cell (1 × 1) was considered to be the stable reconstruction of α-quartz (001) 8 . Some studies show two reconstructions, (2 × 1) and (2 × 2), comparable in energy 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%